2013
DOI: 10.1093/nar/gkt466
|View full text |Cite
|
Sign up to set email alerts
|

Computational prediction of the localization of microRNAs within their pre-miRNA

Abstract: MicroRNAs (miRNAs) are short RNA species derived from hairpin-forming miRNA precursors (pre-miRNA) and acting as key posttranscriptional regulators. Most computational tools labeled as miRNA predictors are in fact pre-miRNA predictors and provide no information about the putative miRNA location within the pre-miRNA. Sequence and structural features that determine the location of the miRNA, and the extent to which these properties vary from species to species, are poorly understood. We have developed miRdup, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 87 publications
0
73
0
Order By: Relevance
“…The predicted structures were also validated on Wheat MicroRNA Portal (http://wheat.bioinfo. uqam.ca) (Agharbaoui et al 2015;Remita et al 2016) using mirDup (v1.2) (Leclercq et al 2013) with two datasets: all miRBase (B) r20 and Wheat (W) r20.…”
Section: Prediction Of the Secondary Structures Of Mirna Precursorsmentioning
confidence: 99%
“…The predicted structures were also validated on Wheat MicroRNA Portal (http://wheat.bioinfo. uqam.ca) (Agharbaoui et al 2015;Remita et al 2016) using mirDup (v1.2) (Leclercq et al 2013) with two datasets: all miRBase (B) r20 and Wheat (W) r20.…”
Section: Prediction Of the Secondary Structures Of Mirna Precursorsmentioning
confidence: 99%
“…19 Although the latest encouraging research has reported that up-regulated ZFAS1 acts as a promoter for the occurrence of NPC through the activation of the Wnt/β-catenin pathway, the role of ZFAS1 in NPC requires further investigation. [21][22][23] Multiple miRNAs including miR-1, miR-let-7 and miR-138 participate in the tumorigenesis, progression and metastasis of NPC through biological functions, such as inducing apoptosis and inhibiting proliferation. [21][22][23] Multiple miRNAs including miR-1, miR-let-7 and miR-138 participate in the tumorigenesis, progression and metastasis of NPC through biological functions, such as inducing apoptosis and inhibiting proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…20 MiRNAs, a group of short noncoding RNAs, bind to target mRNAs by incomplete complementarity and then inhibit the translation or reduce the stability of target mRNAs. [21][22][23] Multiple miRNAs including miR-1, miR-let-7 and miR-138 participate in the tumorigenesis, progression and metastasis of NPC through biological functions, such as inducing apoptosis and inhibiting proliferation. Recently, miR-892b has been found to be associated with bladder cancer 24 and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The source codes of miRLocator are downloadable from the website (https:// github.com/cma2015/miRLocator). Leclercq et al (2013) reported the use of miRduplex (miRdup) (http://www.cs.mcgill.ca/*blanchem/mirdup/) as an efficient tool for the computational prediction of locating miRNAs within their pre-miRNAs. Ten-fold cross-validation of 5854 experimentally validated miRNAs across 19 plant species highlighted the fact that miRLocator is a better option in predicting mature miRNAs within plant pre-miRNAs than miRdup (Cui et al 2015a).…”
Section: Mirlocatormentioning
confidence: 99%